'I wish I knew more ...' the end-of-life planning and information needs for end-stage fibrotic interstitial lung disease: views of patients, carers and health professionals. Issue 1 (27th September 2012) - Bajwah, Sabrina; Koffman, Jonathan; Higginson, Irene J; Ross, Joy R; Wells, Athol U; Birring, Surinder S; Riley, Julia
Abstract : The importance at the end of life of developing effective communication and meeting information needs is recognised as being central to enhance patient and family centred experience. This qualitative study aimed to explore understanding of the disease, preferences regarding end-of-life planning, and views on communication and coordination of care in patients with Progressive Idiopathic Fibrotic Interstitial Lung Disease (PIF-ILD). Twelve semistructured in-depth qualitative interviews were conducted among PIF-ILD patients and carers attending two London hospitals. Six Interviews were also conducted among health professionals from one London Hospital, a palliative care service and primary care. There was good understanding of the terminal nature of the disease among both patients and carers, but a poor understanding of prognosis, and how the disease would manifest at the end stages. Both patients and carers expressed a wish to receive more information from clinicians. Health professionals recognised the difficulty of balancing information needs with maintaining hope. No participants were aware of any palliative care input, and no participants had considered important end-of-life issues, such as preferred place of care and preferred place of death. Our work shows that palliative interventions need to be developed for this group of patients which should aim to improve communication and coordination of care, while facilitating discussions surrounding information needs and important end-of-life preferences.